2002
DOI: 10.1002/ijc.10215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N‐acetylcysteine in an esophageal carcinogenesis model in rats treated with diethylnitrosamine and diethyldithiocarbamate

Abstract: Due to the increasing role of esophageal tumors in human cancer pathology, there is need for animal models evaluating the mechanisms of esophageal carcinogenesis and investigating protective factors toward this disease. Several N-nitrosamines have been shown to induce esophageal tumors in rats. We designed a study in BD 6 rats treated with N-diethylnitrosamine (DEN) according to a simple protocol involving weekly i.p. injections of this carcinogen for 8 consecutive weeks. This treatment resulted in a high inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In other liver carcinogenesis models, NAC (10–100 mg/kg body weight p.o. 5x/wk) inhibited the induction of PGST-positive foci by 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx) in rats (Nishikawa-Ogawa et al , 2006), but did not affect the induction of liver tumors in rats treated with DEN and diethyldithiocarbamate when administered at 400 mg/kg body weight/day in drinking water (Balansky et al , 2002). Resveratrol, injected at a dose of 1 mg/kg body weight/day i.p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other liver carcinogenesis models, NAC (10–100 mg/kg body weight p.o. 5x/wk) inhibited the induction of PGST-positive foci by 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx) in rats (Nishikawa-Ogawa et al , 2006), but did not affect the induction of liver tumors in rats treated with DEN and diethyldithiocarbamate when administered at 400 mg/kg body weight/day in drinking water (Balansky et al , 2002). Resveratrol, injected at a dose of 1 mg/kg body weight/day i.p.…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemicals selected for this study were ellagic acid, β-carotene, curcumin, N-acetyl cysteine (NAC), coenzyme Q 10 (CoQ10), resveratrol, lycopene, and a tea extract containing epigallocatechin-3-gallate (EGCG). All of these agents have been found to inhibit experimental carcinogenesis in several studies (Wood et al , 1982; Mukhtar et al , 1986; Suzuki et al , 1986; Toma et al , 1995; Yang et al , 2001; Balansky et al , 2002; Nishino et al , 2002; Yang et al , 2002; Hannum, 2004; Joe et al , 2004; Russell, 2004; Bhuvaneswari and Nagini, 2005; Perumal et al , 2005; Nishikawa-Ogawa et al , 2006; Sakano et al , 2006; Thangapazham et al , 2006). Ellagic acid is a naturally occurring plant phenol that has strong scavenging ability for hydrogen peroxide, superoxide anion and hydroxy anion in vitro (Cozzi et al , 1995; Iino et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, N-acetylcysteine has desirable properties for long-term use. The discovery that N-acetylcysteine can prevent mutagenesis by oxidative DNA damage [27][28][29] and decrease the incidence of pre-neoplastic and neoplastic lesions by various smoke-related chemical carcinogens in rodents [23,[30][31][32] pointed to its chemopreventive potential. Unfortunately, clinical trials did not indicate Nacetylcysteine to be effective in preventing lung cancer in smokers [33].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that N-nitroso compounds and their precursors are among the etiological factors for SCC in the SCC-dominated areas. Nitrosamines have very high organ specificity and have been used as tumor inducing agents in several murine models [6,[9][10][11]. N-nitrosomethylbenzylamine (NMBA) is a potent esophageal carcinogen in rats [12].…”
Section: Introductionmentioning
confidence: 99%